2010
DOI: 10.1590/s0080-62342010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Estressores em Unidade de Terapia Intensiva: versão brasileira do The Environmental Stressor Questionnaire

Abstract: The objective of the present study was to perform the cultural adaptation of The Environmental Stressor Questionnaire -ESQ for the Brazilian Portuguese, as well as to verify its reliability and validity. In order to ensure the equivalence between the original instrument and the Brazilian version, all methodological steps recommended in the literature regarding cultural adaptation were followed. The Brazilian version of the ESQ was applied to 106 ICU patients in two hospitals (public and private) in the interio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
0
8
0
11
Order By: Relevance
“…However, in this study there was no significant association between pain and age, which is equivalent to the recent study in which elderly patients also demonstrated greater tolerance to discomforts resulting from hospitalization, including pain. (18) There was no statistical relevance between intensity of behavioral pain and gender, type of hospitalization (clinical/surgical) and clinical outcome (p>0.05).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, in this study there was no significant association between pain and age, which is equivalent to the recent study in which elderly patients also demonstrated greater tolerance to discomforts resulting from hospitalization, including pain. (18) There was no statistical relevance between intensity of behavioral pain and gender, type of hospitalization (clinical/surgical) and clinical outcome (p>0.05).…”
Section: Discussionmentioning
confidence: 92%
“…The male gender, age under 60 years old, and mean time of 10.7 days of hospitalization of patients in this study corroborate with recent studies. (12,17,18) The prevalent specialty (neurology) can be justified according to the profile of the studied hospital that is a reference in the care of polytrauma patients, and traumatic brain injury (TBI) is the predominant diagnosis in these hospitalizations, which also justifies the higher incidence of surgical hospitalizations (72.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Este, a su vez, exige una adaptación física y/o psicológica en el individuo. (5) Cabe destacar que para que haya estrés, se necesita la existencia de un factor estresante o estresor. Estos pueden presentar diversas características en la causa del estrés, pero el cuerpo se manifiesta de la misma manera, sea cual fuere la fuente.…”
Section: Introductionunclassified
“…Em decorrência da gravidade que envolve os quadros de pacientes que são tratados na UTI, estudos têm apontado que este ambiente acaba se tornando um espaço gerador de ansiedades, angústias, tristeza, estresse 1,3,4,5,6 . A emergência de tais sentimentos é compartilhada muitas vezes por profissionais 7 e, principalmente, por familiares 8 e pacientes 5,7,9,10 , o que contribui para o fortalecimento de crenças, significados e percepções que conferem a UTI um caráter mórbido e sombrio.…”
unclassified